X= 3 y=3
(3)2x+y=9
4x-3y=3
6x+3y=27
4x-3y=3
——————
10x=30
—————-
10
x=3
2(3)+y=9
6+y=9
-6. -6
y=3
This is a geometric sequence, so use the formula for the sum of a geometric sequence:
Sum = (a(r^n - 1))/(r - 1)
where a is the first term, -5
r is the common ratio, 5
and n is the number of terms
Thus,
Sum = ((-5)(5^6 - 1))/(5-1) = -19530
Answer:
help u with what? Say what u need
PLEASE PLEASE PLEASE PLEASE (5'1, 5'2, 5'3, 5'4, 5'5, 5'6, 5'7, 5'8, 5'9, 5'9, 5'10, 5'11, 5'12)
Yakvenalex [24]
Answer:5
5 feet 7 inches
Step-by-step explanation:
first add all of the given together and then divide what you get by the number of terms given
(5'2+5'3+5'4+ 5'5+5'6+ 5'7+ 5'8+5'9+5'9,+5'10+5'11+5'12)/12 = 5'7 11/64 inches
then divide 11 by 64 on a calculator and then round the decimal you get to the nearest tenth which gives you the answer 5 feet 7 inches.